Taxation in developing countries: Case study of Cameroon - Samuel Fambon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
In the beginning of the 1980s, Cameroon witnessed a sustained rate of growth, associated essentially with the boom in the oil sector. Increased budgetary and extra-budgetary resources generated by this sector helped to raise the investment rate in the economy, and to maintain a reasonable level of external indebtedness. But after this period of expansion, the country experienced unfavourable economic development caused by a successive decline in the terms of trade, leading to profound imbalances, notably in public finance and the external account. The government subsequently initiated a series of measures to reform its tax system and to adapt it to national economic realities. An efficient and equitable taxation encourages production and the accumulation of national wealth stimulates saving and investments and hence job creation. Such a tax system could, therefore, ensure sustainable growth and development in Cameroon. The study aims to contribute to a better understanding of the evolution of the tax system in Cameroon. In particular, the paper reviews the chronology of the main tax reforms and the evidence on the distributional aspect of taxation. Investigating the issues involved with tax administration and decentralization in the country and local government finances, it also attempts to explore the problems and successes associated with the implementation of tax reforms.
Keywords: O55; H20; H22; H24; H29; 330; tax reform; Cameroon; incidence; impact analysis; Steuersystem; Steuerreform; Kamerun